2009
DOI: 10.1007/s00442-009-1479-6
|View full text |Cite
|
Sign up to set email alerts
|

Fine root decomposition rates do not mirror those of leaf litter among temperate tree species

Abstract: Elucidating the function of and patterns among plant traits above ground has been a major research focus, while the patterns and functioning of belowground traits remain less well understood. Even less well known is whether species differences in leaf traits and their associated biogeochemical effects are mirrored by differences in root traits and their effects. We studied fine root decomposition and N dynamics in a common garden study of 11 temperate European and North American tree species (Abies alba, Acer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
212
6
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(232 citation statements)
references
References 39 publications
9
212
6
5
Order By: Relevance
“…However, there was a significantly positive correlation between fine root decomposition rate and soil temperature, which was, therefore, the major driver of fine root decomposition, similar to that found in previous studies [57,[62][63][64][65][66]. According to Cusack et al [62], precipitation-related parameters are strong predictors of litter decomposition in neotropical forests, and Hobbie et al [67] also suggested that moister soils could facilitate rapid mass loss by promoting leaching and microbial activity or a faster colonisation of decomposing material by microbes. Moreover, Zhang et al [68] and Violita et al [69] stated that the decomposition rate of roots increased with increasing internal Ca concentration in roots.…”
Section: Soil Factors Influences On Fine Root Traitssupporting
confidence: 77%
“…However, there was a significantly positive correlation between fine root decomposition rate and soil temperature, which was, therefore, the major driver of fine root decomposition, similar to that found in previous studies [57,[62][63][64][65][66]. According to Cusack et al [62], precipitation-related parameters are strong predictors of litter decomposition in neotropical forests, and Hobbie et al [67] also suggested that moister soils could facilitate rapid mass loss by promoting leaching and microbial activity or a faster colonisation of decomposing material by microbes. Moreover, Zhang et al [68] and Violita et al [69] stated that the decomposition rate of roots increased with increasing internal Ca concentration in roots.…”
Section: Soil Factors Influences On Fine Root Traitssupporting
confidence: 77%
“…in some places the moraine was within plowing depth, in others it was not). Previous studies documented that leaf and fine root chemistry, lifespan, and litter fluxes vary by as much as two-fold or more among the 14 tree species (Hobbie et al 2010;Reich et al 2005;Withington et al 2006). …”
Section: Study Sitementioning
confidence: 99%
“…In contrast, the impact of trees on the net redistribution of nutrients from soils to plants is perhaps more a function of variation in the concentrations and pools of nutrients in wood. Notably, tree species with high nutrient concentrations in leaf litter do not necessarily have high nutrient concentrations in roots (Hobbie et al 2010) or wood, so different tissues and organs of the same species can have unique effects on soil nutrient mineralization and redistribution.…”
Section: Introductionmentioning
confidence: 99%
“…Soil C reduced to a greater extent in a litter exclusion treatment than in a root exclusion treatment in a black cherry-sugar maple forest (Bousson Environmental Research Reserve, Pennsylvania, USA) (Bowden et al, 2013). It is not clear what controls the relative importance of aboveground and belowground litter contributions to soil C. Root and leaf litter decompose at different rates (Hobbie et al, 2010), and may produce different organic compounds that undergo different rates of chemical (Hassink, 1997) and physical (Six et al, 2002, Pronk et. al., 2013 protection.…”
Section: Changes In Soil Total Carbon Concentrationmentioning
confidence: 99%